Sexuality and psychological well-being in different polycystic ovary syndrome phenotypes compared with healthy controls: a cross-sectional study - Fatemeh Bahadori; Shahideh Jahanian Sadatmahalleh; Ali Montazeri; Malihe Nasiri (BMC, 2022)
Abstract Introduction Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. The present study aimed to compare the women with different PCOS phenotypes with the healty group in terms of sexual function, depression, anxiety and quality of life scale. Materials and methods The present cross-sectional study was carried out on 192 women with PCOS (classified on the basis of Rotterdam criteria into four categories) and 50 healthy controls. All participants were asked to fill out the valid and reliable questionnaires of FSFI (Female Sexual Function Index), HADS (Hospital Depression and Anxiety Scale) and SF-12. Results In the HADS questionnaire, phenotype B achieved the highest mean score in anxiety and depression domains, whereas, phenotype B had the lowest mean score in the FSFI and SF-12 quassionnaires. Furthermore, there was a significant difference between the women with PCOS phenotypes and the control grroup in arousal, lubrication, pain, and mean total score of FSFI (P < 0.05). In regression logistic analysis, age, infertility and depression were predictors of sexual dysfunction (P < 0.05). Conclusion The results indicated significant differences in terms of sexual dysfunction, depression, anxiety and quality of life in the women suffering from different phenotypes of PCOS compared with the healthy group. These results provide evidence that care and recommendations for improving women's QoL and sexual function should be considered according to the relevant PCOS phenotypes.